Preface: 5th International Conference on Education, Sport and Psychological Studies (ESPS 2024) - Chen, Shan; Wu, Xi (Transactions on Social Science, Education and Humanities Research, 2024)
This proceeding includes original and peer-reviewed research papers from the 5th International Conference on Education, Sport and Psychological Studies (ESPS 2024) held on May 25-26, 2024 in Hong Kong, China.The aim of the conference is to provide an interactive platform for the academicians, R & D organizations, industries, innovators, entrepreneurs, government agencies and policy-makers etc., from both China and abroad to exchange ideas on recent researches and advances in the domain of Education, Sport and Psychological Studies with its prospective application in the various interdisciplinary domains of engineering. This two-day conference is being organized online in technical association with Research Center of Engineering and Science and will include invited keynote talks and oral paper presentations from both academia and industry to ignite our young minds, to initiate them in the field of meaningful research and thereby enrich their existing knowledge.By submitting a paper to ESPS 2024, the authors agreed to the review process and understood that papers undergo a peer-review process. Manuscripts were reviewed by appropriately qualified experts in the field selected by the Conference Committee, who gave detailed comments and-if the submission was accepted the authors would submit a revised version that considered this feedback. All papers were reviewed using a double-blind review process: authors declared their names and affiliations in the manuscript for the reviewers to see, but reviewers did not know each other’s identities, nor did the authors receive information about who had reviewed their manuscript. The Committees of ESPS 2024 invested great efforts in reviewing the papers submitted to the conference and organizing the sessions to enable the participants to gain maximum benefit.Shan Chen, Xi WuConference Committees